Does culinary tourism represent an opportunity to enhance the agri-food heritage? The case of the historical center of Quito - Sosa-Sosa, María Elena; Thomé-Ortiz, Humberto (Revista de Estudios Andaluces, 2020)
The aim of this paper is to identify the manner in which emblematic restaurants are related with the agri-food heritage of Quito from the connection with small local producers. Based on a case study, an analysis was made around empirical observations and secondary sources. The results show that the food offered tend to be acquired from large suppliers of remote areas, decoupling from the local agricultural sector. It is concluded that tourism can play an important role in the equal distribution of income among the diverse economic participants of the sector and in the continuity of the local agri-food systems. For this, the coordination between the tourist and agri-food industries is fundamental, starting with the logic of local commerce.